Veil journeys unveiled: Exploring muslim women’s veil experiences among malaysian women in France - Mohamed Foudi, Nurin Syazwani Farahin; Wan Mohtar, Wan Ikhlas (EDUCATUM Journal of Social Sciences, 2025)
Muslim women’s experiences with the veil in France elicits diverse feedback yet little research has been conducted on the veil experience of Southeast Asian Malaysian Muslim women who have resided in France for more than a year. In response to this gap, the study identifies the controversial meanings of veiling experiences and explores the complexities of veiling practices among Malaysian Muslim women in France. Six Malaysian Muslim women residing in France were interviewed. Interpretive phenomenological analysis approach (IPA) revealed that Malaysian Muslim women in France shared accounts of receiving respect, finding acceptance within their work environments, and encountering a general atmosphere of tolerance towards their religious and cultural identities. They also believed that the opinion of the locals in France towards the act of veiling are different depending on their geographical location. Some interviewees are certain that the locals in rural areas are more paranoid of women in veils than the locals in urban areas. The findings support the importance of exploring the discourse of veiling experiences among Malaysian women in France and the need to highlight the intersection of cultural practices, religious identity, and the challenges faced by Muslim women who choose to wear the veil while residing in a non-predominant Muslim country like France.